Determinants of SME Tax Compliance: The Role of Accounting Knowledge and Taxpayer Attitudes - Tisha Alfira; Ezra Ivana Cecilia; Yanti Br Siregar; Annisa Nauli Sinaga; Yanson Pane (YAYASAN BINA BISNIS NUSANTARA MEDAN, 2026)
This study examines to analyze the effect of accounting conservatism, sales growth, thin capitalization, transfer pricing, and financial distress on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange (IDX). This research employs a quantitative approach using secondary data obtained from companies’ financial statements and annual reports. The population consists of all energy sector companies listed on the IDX, with purposive sampling used to select 23 companies as research samples, resulting in a total of 69 observations. The data were analyzed using multiple linear regression analysis, preceded by classical assumption tests including normality, multicollinearity, autocorrelation, and heteroscedasticity tests. The results indicate that accounting conservatism, sales growth, thin capitalization, transfer pricing, and financial distress simultaneously affect tax avoidance. Partially, transfer pricing and financial distress have a positive and significant effect on tax avoidance, while accounting conservatism, sales growth, and thin capitalization do not have a significant effect on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange